Calcium carbonate nanoparticles loaded with thymoquinone derived from medicine food homology plants combined with 5-fluorouracil for colon cancer Treatment: Proteomic and metabolomic insights - Deng, Xi; Abu Bakar, Md Zuki; Yang, Zhongming (Elsevier, 2025)
Colon cancer is a malignant tumor posing a significant threat to global human health, and its effective treatment remains a major challenge. In this study, we explored the potential of combining calcium carbonate nanoparticles loaded with thymoquinone, a bioactive compound derived from the medicine food homology plant Nigella sativa, with the chemotherapeutic agent 5-fluorouracil (5-FU). The therapeutic efficacy of this combination was evaluated using CT26 tumor-bearing Balb/c mice, and its underlying molecular mechanisms were investigated through analytical techniques, including proteomics and metabolomics. Our results demonstrated that thymoquinone-loaded calcium carbonate nanoparticles (TQ-CaCO3np) significantly enhanced the anti-tumor efficacy of 5-FU while mitigating its associated toxicity. Proteomics and metabolomics analyses collectively revealed that the therapeutic benefits of the TQ-CaCO3np and 5-FU co-treatment were primarily mediated through the regulation of 2-oxocarboxylic acid metabolism pathway, biosynthesis of amino acids pathway, and HIF-1 signaling pathway. Six proteins (ACO2, GAPDH, PSPH, PDHA1, PDHB, and RPS6) and nine metabolites (alanine, glutamate, proline, glutamine, threonine, adenosine 5′-triphosphate, lactate, leucine, and isoleucine) were identified as critical targets within these pathways. Bioinformatics analyses, including bulk RNA-seq, single-cell RNA-seq, and immunohistochemical staining, confirmed the clinical relevance of these targets. These findings highlight the potential of combining traditional chemotherapies with bioactive compounds derived from medicine food homology plants and employed with nanobiotechnology, offering new insights into therapeutic strategies for colon cancer and providing the identified targets as potential biomarkers for therapeutic intervention.